A systematic review of the impact of the COVID-19 pandemic on the mental health of adolescents and young people with disabilities aged 15-29 years - Xing Yu Leung; Anne Marie Kavanagh; Que Tien Quang; Marissa Shields; Zoe Aitken (BMC, 2023)
Abstract Background The COVID-19 pandemic has exacerbated the psychological burden on young people around the world and may have disproportionately large impacts for young people with disabilities. This review aims to systematically review the quantitative evidence on the impact of the COVID-19 pandemic on the mental health of young people with disabilities and evaluate the quality of included studies. Methods A systematic search was conducted using 5 electronic databases. The quality of the studies was assessed using the SIGN risk of bias assessment tool. A narrative synthesis was performed to synthesize the results of included studies. Results The initial search yielded 1935 studies, of which two met the eligibility criteria, one longitudinal study and one cross-sectional study, both assessed to be of low quality. In the cross-sectional study, young people with intellectual and developmental disabilities self-reported an increase in mental health symptoms. The longitudinal study found no evidence of a change in mental health symptoms from pre-pandemic to during the pandemic among young people with autism spectrum disorder, although these individuals reported negative impacts of the COVID-19 pandemic on their emotional or mental health. Conclusions The findings of this review provide some weak evidence of a negative impact of the COVID-19 pandemic on the mental health of young people with disabilities. Importantly, the findings highlight the lack of research in this area. More research is needed to investigate the impact of the pandemic on the mental health of young disabled people, in order for governments to develop emergency preparedness plans to safeguard the well-being of this population.